A view on the history of Armenian-Russian relations: lessons of history and reality - Hovhannisyan, Haykaz J.; Menkouski, Viachaslau I. (Journal of the Belarusian State University. History, 2025)
The article revises the history of relations between Armenia and Russia, stages of formation of Armenian-Russian historical ties. The history of Armenian-Russian military-political, economic, cultural and spiritual ties goes back centuries. At the beginning of 19th century, because of military and political events that had taken place in Transcaucasia, Eastern Armenia became a part of the Russian Empire. Since that time, Russia began to play a decisive role in the historical destiny of the Armenian people, a new stage in Armenian-Russian relations began. After Armenia’s accession to Russia, its economic, political and cultural life has significantly advanced, which had been impossible under the domination of Persia and Turkey. The authors of the article conclude that the turbulent events currently taking place in the Caucasus region and throughout the world show that the Armenian nation is again faced with problems that history have already posed. In this regard, the authors are convinced that the materials contained in the article will help readers to assess the political motives and goals of Armenia and Russia based on historical lessons and realities.